2013
DOI: 10.1590/s0103-84782013001100001
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização bromatológica de silagens de milho de genótipos super precoce

Abstract: A disponibilização anual de genótipos de milho é grande, sendo necessária uma adequada avaliação desses genótipos para serem indicados para a produção de silagem. Objetivou-se avaliar as características bromatológicas da silagem produzida a partir de diferentes genótipos de milho, bem como, avaliar se a base genética ou a dureza dos grãos podem alterar a indicação de genótipos de milho para silagem. O experimento foi realizado na área experimental da Universidade Tecnológica Federal do Paraná, no delineamento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
3
1
1
Order By: Relevance
“…The contents of ADF should be equal to or lower than 30% to obtain silage of good quality (Mendes et al, 2008;Neumann, Ost, Pellegrini, & Defaveri, 2008); these values were achieved in the present study in season 1. Thus, Moraes, Jobim, Silva and Marquardt (2013), when comparing and assessing the chemical composition of maize hybrids, obtained ADF values around 28%, confirming the values obtained by Vieira et al (2013), with 29%, and the contents obtained herein.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The contents of ADF should be equal to or lower than 30% to obtain silage of good quality (Mendes et al, 2008;Neumann, Ost, Pellegrini, & Defaveri, 2008); these values were achieved in the present study in season 1. Thus, Moraes, Jobim, Silva and Marquardt (2013), when comparing and assessing the chemical composition of maize hybrids, obtained ADF values around 28%, confirming the values obtained by Vieira et al (2013), with 29%, and the contents obtained herein.…”
Section: Resultssupporting
confidence: 84%
“…In this sense, Moraes et al (2013) and Vieira et al (2013) were successful with the ADF values obtained, with contents below 20%, which, directly affects the apparent digestibility of the forage. In addition.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The ADF values in the present study were higher than those found by Vieira et al (2013b), who reported approximate mean values of 292.9 g kg -1 for several corn genotypes. The ADF is related to forage digestibility because it contains the highest proportion of ADL, which is the fraction of the fiber that exhibits complete indigestibility.…”
Section: Productive Characteristics and Chemical Compositioncontrasting
confidence: 89%
“…; P. C Silva et al, (2003)Souza and Soratto (2006);Storck, Cargnelutti, Lopes, Toebe and Silveira (2009);Tres et al (2014);Velho et al (2006Velho et al ( , 2007;Vieira et al (2013aVieira et al ( , 2013b;Vilela et al (2008); Von Pinho, Vasconcelos, Borges andResende (2007);;Zopollatto et al (2009).…”
mentioning
confidence: 99%